The impact of the Shariah announcement on the stock prices - Siti Hajar, Osman (2024)
This research investigates the impact of Shariah compliance announcements on stock prices in Malaysia from 2019 to 2023. Utilizing event study methodology, the study examines Average Abnormal Return (AAR) and cumulative average abnormal returns (CAAR) to assess stock prices reactions surrounding these announcements. The findings reveal significant negative abnormal returns before the announcements and notable positive abnormal returns afterward. The study highlights the volatility and behavioural patterns in stock prices associated with Shariah delisting announcements, providing critical insights for investors, fund managers, and policymakers regarding the implications of Shariah compliance in the Malaysian stock price.